PENGARUH TIPE KLIEN DAN TIPE KOMUNIKASI TERHADAP PENGUMPULAN BUKTI AUDIT (Studi Persepsi Auditor KAP di Jawa Tengah) - Nur Amalia Fitriani; Anis Chariri (Diponegoro Journal of Accounting, 2014)
This research is replication of research by Bennett and Hatfield (2013) investigating the effect of the social mismatch between auditors and client on the collection of audit evidence. This research aims to examine the effect of client type and communication type on the collection of audit evidence. In addition, this research examines the effect of communication type as moderate between client type on the collection of audit evidence.The population of the research is auditors that work at the firm in the province of Central Java. The sample of the research is junior auditors with sampling techniques using purposive sampling. Data were collected by questionnaire and analyzed by binary logistic regression.The research findings that show client type and communication type negatively influenced the collection of audit evidence. In addition, communication type strengthened the effect of client type on the collection of audit evidence.